A rapid and convenient method for preparative separation of three indissolvable polyphenols from Euphorbia pekinensis by the flexible application of solvent extraction combined with counter‐current chromatography. Issue 14 (18th June 2013) - Gu, Jiamin; Feng, Reihong; Wu, Zhiyuan; Guan, Shuguang; Guo, Jiling; Cheng, Chunru; Xu, Pingping; Zhang, Jingxian; Wang, Yang; Qu, Hua; Man, Wei; Yu, Wenbo; et al.
<x xml:space="preserve">Abstract</x> A rapid and convenient method was established to preparatively isolate the three ellagic acid types of compounds, which were the main polyphenols in Euphorbia pekinensis, by flexibly applying solvent extraction combined with counter‐current chromatography (CCC). The total extract (extracted using 95% ethanol) of E. pekinensis was pretreated by two simple steps before CCC isolation, following the procedure: the total extract was extracted by classical solvent extraction using petroleum ether and ethyl acetate, respectively, and then the ethyl acetate extract was suspended using 95% ethanol, after being allowed to stand overnight, the sediment was obtained. Partial sediment (100 mg) was then directly separated by CCC with a two‐phase solvent system composed of chloroform‐95% ethanol‐water‐85% formic acid (50:50:50:5, v/v/v/v). About 22 mg of 3, 3′‐dimethoxy ellagic acid (1), 12 mg of 3, 3′‐di‐O‐methyl‐4‐O‐(β‐d‐xylopyranosyl)ellagic acid (2), and 35 mg of ellagic acid (3) with purities of 96.0, 95.2, and 95.4% were obtained respectively in one step within 4 h. After being purified by washing with methanol, the purities of the three compounds obtained were all above 98%. The purities were determined by HPLC and their chemical structures were further identified by 1H and 13C NMR spectroscopy. The recoveries were calculated as 84.6, 85.7, and 89.5%, respectively. The result demonstrated that the present isolation method was rapid, economical and efficient for the preparative separation of polyphenols from E. pekinensis.